Knowledge, attitude, and practice assessment regarding osteoporosis among post-menopausal women attending an urban health centre in south India - Nelapati, Sherly Shulamite (International Journal Of Community Medicine And Public Health, 2022)
Background: This study aimed to assess the awareness of osteoporosis in postmenopausal women. Objective was to evaluate knowledge, attitude, and practices about osteoporosis and its correlation among postmenopausal women. Methods: Cross-sectional study was carried out to assess the state of awareness in consecutive postmenopausal women using a validated questionnaire- osteoporosis knowledge assessment tool (OKAT). Results: A total of 300 postmenopausal women were enrolled in this study. In spite of being aware of the consequences of osteoporosis, in most subjects there was a generalized lack of awareness concerning available treatment options and risk factors. We have observed about 40% of had poor awareness about osteoporosis. Conclusions: This study showed an evident deficit in awareness of osteoporosis in postmenopausal women and there’s a need to emphasize educating and aware, women regarding the consequences of osteoporosis.